1962
DOI: 10.1002/anie.196205281
|View full text |Cite
|
Sign up to set email alerts
|

The Isomerization of Aziridine Derivatives

Abstract: Derivatives of aziridine or ethylenimine are isomerized by acids, nucleophilic reagents, or pyrolysis. All of the isomerizations reported so far are ring-opening reactions, predominantly involving cleavage of the carbon-nitrogen bond of the ring, although a few isomerizations are known in which the carbon-carbon bond of the ring is broken. Isomerization of ap-propriate aziridine derivatives provides useful synthetic pathways leading to heterocyclic systems such as oxazolines, imidazolines (and related systems)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
3

Year Published

1970
1970
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 20 publications
1
20
0
3
Order By: Relevance
“…wt. 450.2155): C , 69.31;H;6.71;N, 6.22. Found (450.2142 (mass spectrum)): C, 69.29; H, 6.53; Id, 6.13.…”
Section: Preparation Of Diastereomeric Cis-1-mentlzyl L-p-mentioning
confidence: 98%
See 1 more Smart Citation
“…wt. 450.2155): C , 69.31;H;6.71;N, 6.22. Found (450.2142 (mass spectrum)): C, 69.29; H, 6.53; Id, 6.13.…”
Section: Preparation Of Diastereomeric Cis-1-mentlzyl L-p-mentioning
confidence: 98%
“…When compound 8 was treated with a solution of sodium iodide (15) or potassium thiocyanate in refluxing acetone three products were obtained; the cis-and trans-2-oxazolines (9 and 10) and the unsaturated amide, 11 (see Scheme 3). Compounds 9 and 10 were produced in a ratio of 30:70.…”
mentioning
confidence: 99%
“…[16][17][18] It is obvious from the literature that E/Z isomerization barrier will be much higher for most imines. 19 The detailed investigations of the imine interconversion and the characterization of the new compound 1X are now underway. This was not, however, observed (the observed energy barrier was similar to conjugated imines).…”
Section: The Stereoselective Synthesis and The Nitrogen Interconversimentioning
confidence: 99%
“…Above 403 K, in nitrobenzene there is a competition between the imine interconversion and the aziridine rearrangement. 19 The detailed investigations of the imine interconversion and the characterization of the new compound 1X are now underway. Thus, we attribute the observed 1 H DNMR effect to nitrogen inversion of aziridine ring nitrogen.…”
Section: The Stereoselective Synthesis and The Nitrogen Interconversion Studies Of 2-(tert-butoxymethyl)-1-[n-(4-methylbenzenesulfonyl) (mentioning
confidence: 99%
“…Our initial observations of a chloride-promoted isomerization suggested that the well-known rearrangement of certain N-acyl aziridines (7) should also be possible with the benzylaziridine system 1. If compound 1 could be isomerized to the corresponding oxazoline 6, one would have a useful protecting group for carboxylic acids which incorporates a chromophore for use as a chromatographic marker.…”
mentioning
confidence: 98%